Maternal Death Caused by Severe-Critical COVID-19 in Jakarta: Case Series: Case Series - Djusad, Suskhan; Meutia, Alfa Putri; Suastika, Arresta; Hidayah, Gita Nurul; Surya, Ilham Utama; Priangga, Muhammad; Fadhly, Raden; Harzif, Achmad Kemal (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: As of January 2021, Indonesia had the 21st highest number of total COVID-19 cases and the 17th highest total deaths among all countries. COVID-19 infection in pregnant women seems to negatively affect both maternal and neonatal outcomes. CASE REPORT: We describe four cases of pregnant women confirmed with severe and critical COVID-19 that resulted in maternal death from November until December 2020. The first case was complicated with thrombocytopenia, her condition quickly deteriorated post-delivery. Pulmonary embolism was suspected as the cause of death. Second and third cases were complicated with preeclampsia, obesity, and advanced maternal age. Second case came in sepsis condition. Her SARS CoV-2 RTPCR swab test came out after her death. Third patient did not have COVID-19 symptoms at admission. She starts having symptoms on second day and was confirmed positive a day after. She falls in septic shock. Fourth patient has history of fever, cough, and dyspnea. She was confirmed positive on first day and her condition worsened, diagnosed with bacterial co-infection sepsis on day eight. All patients underwent cesarean section. CONCLUSION: Limited information and studies for COVID-19 management in pregnant women are challenging for obstetricians. Management should be individualized weighing the benefit and risks in presence of comorbidities or accompanying disease.